A compact miniaturized star fractal antenna for modern wireless applications - Ibrahime Hassan Nejdi; Aziz El Fatimi; Youssef Rhazi; Mustapha Ait Lafkih; Seddik Bri; A. V. Senthil Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this paper, six-band resonant fractal antenna architecture is proposed and fabricated. The ultimate shape is established after six iterations. The resonator is starshaped, and each iteration, a hexadecagon shape from the resonator is subtracted. The antenna is designed and calculated by the numerical simulation based on the finite element method (ANSYS HFSS) and finite integration technique (CST studio). The experimental measurements were performed by the vector network analyzer AVR ROHDE AND SCHWARZ ZVB20. The gain is 4.85 dB, and the bandwidth is 0.33 GHz. The antenna’s structure allows it to work effectively in the GSM, DCS, LTE, WiMAX, WLAN, and C bands. The designed patch has a compact size of (75×75×1.6) mm3 uses as a support the FR-4 substrate for wireless equipment.